Perancangan Game Visual Novel Sebagai Media Pembelajaran Alternatif Pengenalan Asal Usul Aksara Jawa Pada Gen Z - Purwanto, Syaila; Harditama, Marwah Mahayaidha; Prasetya, Miranda Rizky; Ulhaq, Achsanul Khluq Banis Dhiya; Wicaksono, Muhammad Raditya (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
The visual novel "Aji Saka and the Origin of Javanese Script" is designed as a digital-based interactive media to introduce local culture, especially the origin of Javanese script, to the younger generation, especially Generation Z. Generation Z is a group that was born and grew up in the digital era with characteristics that are very familiar with technology, social media, and interactive applications, so they have a more effective learning style through digital and visual media. This game was developed using the Multimedia Development Life Cycle (MDLC) method which consists of six systematic stages, from concept to distribution. The final product is an educational interactive media that presents the legend of Aji Saka in the form of an interesting visual and textual narrative. User evaluation shows a significant increase in understanding with an average of 4.538/5 (90%), as well as a positive user experience in terms of usability.